Czynniki determinujące proces konwergencji gospodarek państw członkowskich Unii Europejskiej ze szczególnym uwzględnieniem Polski w świetle teorii - Młynarzewska, Izabela (The Major Factors Determining the Convergence Process Among EU Countries with a Special Emphasis of Poland, 2008)
Convergence hypothesis is often discussed not only from theoretical but also from practical point of view. Among the determinants of this process are factors directly connected with regional integration process, especially capital and technology flows. The most significant is technological progress, identified with "Solow's rest", which influences the level of Total Factor Productivity (TFP). According to the experiences of Ireland, Greece, Portugal, and Spain, the convergence process among European Union countries is mainly a result of TFP growth, not capital accumulation; therefore, productivity convergence appears and stimulates real convergence process. The source of economic growth in Poland is also TFP growth, so it is possible that the process of Poland's "catching-up" will run in the same way as in the "cohesion" countries. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 19, s. 125-137